New alliances: Plurilateral initiatives as a mode of cooperation in international climate politics - Marian Feist (Stiftung Wissenschaft und Politik (SWP), 2023)
Plurilateral initiatives are again gaining importance in climate diplomacy as a complement to multilateral efforts - not least in view of the lack of progress in implementing the Paris Agreement and more difficult conditions in the UN process. New alliances are expected to facilitate agreement within smaller groups of countries wishing to lead by example and to effectively advance climate action with ambitious goals and more stringent measures. This, in turn, can have an impact beyond individual initiatives and provide normative pressure and incentives for additional states to cooperate. However, plurilateral alliances cannot necessarily overcome the structural challenges that hamper more effective international climate cooperation. In light of this, German and European climate diplomacy should anticipate the specific procedural challenges of individual initiatives, set priorities among the various options, and aim to specify the mandate and design of individual initiatives early on.
Keywords: 320; climate diplomacy; decarbonisation; Germany; European Union; United States; Paris Agreement; UN process; climate summit in Glasgow (COP 26); G7 summit Elmau; Nationally Determined Contributions (NDCs); Common But Differentiated Responsibilities (CBDR)